Predictors of Coronary Lesions Complexity in Patients With Stable Coronary Artery Disease. (May 2013) - Aksakal, Enbiya; Tanboga, Ibrahim Halil; Kurt, Mustafa; Kaya, Ahmet; Topcu, Selim; Kalkan, Kamuran; Sevimli, Serdar
Only a few studies focused on the predictors of the SYNTAX score (SS). We evaluated the independent clinical predictors of SS in 436 consecutive patients with stable angina pectoris who underwent coronary angiography. Estimated glomerular filtration rate (eGFR) was calculated. The mean SS was 25.8 ± 13.7. High-sensitivity C-reactive protein and low-density lipoprotein cholesterol levels gradually rise while high-density lipoprotein cholesterol (HDL-C), triglycerides, and eGFR levels gradually decline from low to high SS tertile. Multivariate logistic regression analysis revealed that diabetes ( P = .005), left ventricular ejection fraction ([LVEF]; P < .001), previous statin use ( P = .02), HDL-C level ( P < .001), and eGFR ( P < .001) were independent predictors of SS. In conclusion, the presence of diabetes mellitus, no previous statin use, and lower values of HDL-C, LVEF, and eGFR were independent predictors of coronary heart disease complexity. This study has been accepted to present at the 28th Turkish National Cardiology Congress.